Twin embryos in the larger benthic foraminifer Nephrolepidina praemarginata - Benedetti, Andrea (Journal of Mediterranean Earth Sciences, 2015)
Twin embryos were recovered in Nephrolepidina praemarginata populations from the upper Rupelian of the Caltavuturo Formation (Sicily). Biometric data and photographic evidences suggest that Siamese-twins embryos result from joined cells produced from the same reproductive cyst during the multiple fissions. The fusion of juveniles may occur before the complete calcification of the first chamber walls and before the release by the parent cell. The frequency of the twin embryos, commonly related to stressed conditions, such as high salinity, water motion, pollution, low pH etc., can be linked also to the reproductive strategies. In unpolluted environments, the occurrence of multiembryonic individuals is herein explained as related to the extreme depths of the total distribution range of a larger foraminiferal taxon, where asexual reproduction and r-strategy dominate far from the ecological optimum.